Effects of indenter angle on micro‐scale fracture toughness measurement by pillar splitting. Issue 12 (4th August 2017) - Ghidelli, Matteo; Sebastiani, Marco; Johanns, Kurt E.; Pharr, George M.
Abstract: We present improvements to a recently developed pillar splitting technique that can be used to characterize the fracture toughness of materials at the micrometer scale. Micro‐pillars with different aspect ratios were milled from bulk Si (100) and TiN and CrN thin films, and pillar splitting tests were carried out using four different triangular pyramidal indenters with centerline‐to‐face angles varying from 35.3° to 65.3°. Cohesive zone finite element modeling (CZ‐FEM) was used to evaluate the effect of different material parameters and indenter geometries on the splitting behavior. Pillar splitting experiments revealed a linear relationship between the splitting load and the indenter angle, while CZ‐FEM simulations provided the dimensionless coefficients needed to estimate the fracture toughness from the splitting load. The results provide novel insights into the fracture toughness of materials at small‐scales using the pillar spitting technique and provide a simple and reliable way to measure fracture toughness over a broad range of material properties.